Inhibitory roles for SHP-1 and SOCS-3 following pituitary proopiomelanocortin induction by leukemia inhibitory factor - Bousquet, Corinne; Susini, Christiane; Melmed, Shlomo (The Journal of clinical investigation, 1999)
Leukemia inhibitory factor (LIF) is a pleiotropic cytokine that stimulates the hypothalamo-pituitary-adrenal (HPA) axis through JAK-STAT activation. We show here that LIF-induced JAK2 and STAT3 tyrosine phosphorylation is transient, disappearing within 20 and 40 minutes, respectively. LIF activates the SH2 domain-containing tyrosine phosphatase, SHP-1, with maximal stimulation observed at 30 minutes. SHP-1 is constitutively associated with JAK2, and LIF induces recruitment of phosphorylated STAT3 to this complex. Overexpression of wild-type or dominant negative forms of SHP-1 shows decreased or increased LIF-induced proopiomelanocortin (POMC) promoter activity, respectively. LIF-induced JAK2 and STAT3 dephosphorylation is delayed until after 60 minutes in cells that overexpress the mutant SHP-1. In addition, SOCS-3, a negative regulator of LIF signaling, binds to JAK2 after 60 minutes of LIF stimulation, after which the complex is degraded by the proteasome. SOCS-3 overexpression blocks LIF-induced JAK2 tyrosine phosphorylation, confirming a role for SOCS-3 in deactivating JAK2 by direct association. Using SOCS-3 fusion proteins, we also define regions of the SOCS-3 protein that are critical for inhibition of LIF-induced POMC promoter activity. Corticotrophic signaling by LIF is thus subject to 2 forms of negative autoregulation: dephosphorylation of JAK2 and STAT3 by the SHP-1 tyrosine phosphatase, and SOCS-3-dependent inactivation of JAK2.